2021
DOI: 10.1002/hep.31600
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl Oxidase‐Like 4 Fosters an Immunosuppressive Microenvironment During Hepatocarcinogenesis

Abstract: Background and Aims Lysyl oxidase‐like 4 (LOXL4) is an amine oxidase that is primarily involved in extracellular matrix remodeling and is highly expressed in HCC tissues, but its functional role in mediating liver carcinogenesis is poorly understood. Therefore, we aimed to investigate the role of LOXL4 in hepatocarcinogenesis. Approach and Results Here, we demonstrate that hepatic LOXL4 expression was increased during the liver carcinogenesis in mice concomitantly fed a choline‐deficient, l‐amino acid–defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 46 publications
0
65
0
Order By: Relevance
“…On the other hand, intercellular transfer of exosome-LOXL4 from HCC to human umbilical vein endothelial cells (HUVEC) promotes angiogenesis, as evidenced by increased HUVEC migration and tube formation [ 57 ]. More recently, Tan et al identified LOXL4 as a key factor in forming an immunosuppressive microenvironment for HCC [ 15 ]. The expression of LOXL4 was increased in a mouse model with liver carcinogenesis induced by a choline-deficient, L-amino acid-defined (CDAA) diet.…”
Section: Roles Of Loxl4 In Tumor Microenvironment and Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, intercellular transfer of exosome-LOXL4 from HCC to human umbilical vein endothelial cells (HUVEC) promotes angiogenesis, as evidenced by increased HUVEC migration and tube formation [ 57 ]. More recently, Tan et al identified LOXL4 as a key factor in forming an immunosuppressive microenvironment for HCC [ 15 ]. The expression of LOXL4 was increased in a mouse model with liver carcinogenesis induced by a choline-deficient, L-amino acid-defined (CDAA) diet.…”
Section: Roles Of Loxl4 In Tumor Microenvironment and Progressionmentioning
confidence: 99%
“…Specifically, LOXL4-harboring exosomes are primarily internalized in hepatic macrophages to shape an immunosuppressive phenotype, such as up-regulated programmed cell death 1 ligand 1 (PD-L1) expression, which further acts to suppress the activity of CD8 + T cells. The mechanism underlying the immunosuppressive role of LOXL4 on shaping macrophage phenotype lies in an H 2 O 2 -dependent activation of the interferon alpha and beta receptor subunit-1-signal transducer and activator of transcription 1 and 3-programmed death-ligand 1 (IFNAR1-STAT1/3-PD-L1) pathway [ 15 ]. The emerging role of LOXL4 in guiding the progression and modeling the microenvironment of HCC is summarized in Table 4 .…”
Section: Roles Of Loxl4 In Tumor Microenvironment and Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, exosomes derived from a variety of cells in the tumor microenvironment can regulate the loss of antitumor effects of CD8 + T cells. Both LOXL4 and miR-23a-3p derived from HCC cells can be delivered by exosomes and activate the expression of PD-L1 in hepatic macrophages after the exosomal internalization, thereby further inhibiting the function of CD8 + T cells or promoting their apoptosis [125,142].…”
Section: T Cellmentioning
confidence: 99%
“…Elevated levels of LOXL4 were found to correlate with poor survival of HCC patients. Thus, in this study, proteomics shed light on the molecular mechanism of LOXL4 during the development of HCC, and also provided new ideas for possible therapeutic intervention [ 62 ].…”
Section: Proteomics the Current Statusmentioning
confidence: 99%